Do ‘Kafeteria Sihat’ attributes influence customers’ post purchase behaviour? / Abdul Rais Abdul Rahman, Chemah Tamby Chik, Mohd Salehuddin Mohd Zahari - Abdul Rahman, Abdul Rais; Tamby Chik, Chemah; Mohd Zahari, Mohd Salehuddin (Universiti Teknologi MARA Selangor, 2018)
‘Kafeteria Sihat’ is a government effort to create a wider choice of healthy eateries, encourage healthy eating practices thus potentially reducing the prevalence of non-communicable diseases (NCD). Past studies of healthy cafeteria programmes have only focused on measuring the customers satisfaction based on the attributes at the cafeteria and the influence of eating behaviour. This study is proposed to evaluate the impact of various ‘Kafeteria Sihat’ attributes on the customers post-purchase behaviour together with perceived value as the moderator as well as eating behaviour and satisfaction as mediators. Using newly developed questionnaires, the survey is expected to be conducted at the 11 public hospitals in Selangor and Putrajaya, Malaysia. The findings of this study will reveal the overall customers’ acceptance of the ‘Kafeteria Sihat’ programme and explain the possible causal relationship between its’ attributes and customers post-purchase behaviour. In addition, moderating and mediating effect of perceived value, eating behaviour and customer satisfaction on the causal relationship are expected to be reported. The findings will not only benefit ‘Kafeteria Sihat’ customers and operators but also for the Ministry of Health in making improvements to the ‘Kafeteria Sihat’ initiative.